1997
DOI: 10.2307/2265876
|View full text |Cite|
|
Sign up to set email alerts
|

Temporal Variation in Cyprid Quality and Juvenile Growth Capacity for an Intertidal Barnacle

Abstract: Implicit in past studies of recruitment is the assumption that all new recruits possess the same capacity for juvenile growth, and that observed variation in juvenile growth and survival is due entirely to spatial and temporal variation in food availability, magnitude of physical stresses, and intensity of competition and predation. We set out to determine if daily larval cohorts of the barnacle Semibalanus balanoides differ in mean physiological quality and, therefore, in their potential for recruiting to adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
1
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(100 citation statements)
references
References 24 publications
6
90
1
3
Order By: Relevance
“…We found that size at settlement and post-metamorphic juvenile growth capacity of D. polymorpha varied considerably among individuals recruiting to a particular population on different dates. These results are consistent with the results of Jarrett & Pechenik (1997), who observed temporal variations in growth capacity of field-collected daily cohorts of marine barnacles. As all of their, and our, post-metamorphic animals were reared at constant temperatures and food concentrations, and divergent post-metamorphic growth was found, we conclude that these distinctions are due to intrinsic differences in the animals' physiological growth capacity.…”
Section: Discussionsupporting
confidence: 92%
“…We found that size at settlement and post-metamorphic juvenile growth capacity of D. polymorpha varied considerably among individuals recruiting to a particular population on different dates. These results are consistent with the results of Jarrett & Pechenik (1997), who observed temporal variations in growth capacity of field-collected daily cohorts of marine barnacles. As all of their, and our, post-metamorphic animals were reared at constant temperatures and food concentrations, and divergent post-metamorphic growth was found, we conclude that these distinctions are due to intrinsic differences in the animals' physiological growth capacity.…”
Section: Discussionsupporting
confidence: 92%
“…Since cyprids do not feed, the energetic reserves accumulated during the naupliar stages are important, as demonstrated by Hentschel & Emlet (2000). Energy accumulated during the naupliar stages affects the larva's capacity to locate a substratum and to settle and metamorphose successfully (Jarrett & Pechenik 1997, Miron et al 2000, Jarrett 2003. Balanus amphitrite (Darwin) cyprids lose their settlement selectivity with age (Rittschof et al 1984), a phenomenon tentatively explained by the 'desperate larva hypothesis' (Toonen & Pawlik 1994).…”
Section: Introductionmentioning
confidence: 99%
“…O assentamento será infl uenciado por: 1) a qualidade fi siológica da larva (conteúdo energético, competência) (Jarret & Pechenik 1997), e 2) o comportamento da larva frente a estímulos tais como: fl uxo d'água, tipo de substrato e textura (Wethey 1986, Abelson & Denny 1997, Walters et al 1999, Todd 2003, sinais químicos (Tamburri et al 1996, Wright & Boxshall 1999, Steinberg et al 2002, biofi lme , Thiyagarajan et al 2006, composição da comunidade residente (Osman & Whitlatch 1995, Jenkins & Hawkins 2003, presença de conspecífi cos (Toonen & Pawlik 1994, Keough 1998.…”
Section: Fatores Que Influenciam a Escolha Do Substrato Para O Assentunclassified
“…Porém, trabalhos recentes demonstraram que características intrínsecas das larvas tais como a condição fi siológica e conteúdo energético podem modifi car: 1) o comportamento de busca de substrato para o assentamento , Toonen & Pawlik 2001, 2) o sucesso durante a metamorfose (Toonen & Pawlik 2001) e 3) a sobrevivência dos recrutas (Jarret & Pechenik 1997, Jarret 2003. Em condições de laboratório, foi demonstrado que o conteúdo orgânico de cipris (larvas competentes para o assentamento) da espécie Semibalanus balanoides e a capacidade de crescimento dos juvenis produzidos variaram em uma escala temporal curta (poucos dias dentro da mesma estação reprodutiva).…”
Section: A Qualidade Fisiológica Da Larva E Sua Importância No Assentunclassified
See 1 more Smart Citation